Combining stereotactic radiosurgery and systemic therapy for brain metastases: a potential role for temozolomide - Hardee, Matthew E.; Formenti, Silvia C. (Frontiers in Oncology, 2012)
Brain metastases are unfortunately very common in the natural history of many solid tumors and remain a life-threatening condition, associated with a dismal prognosis, despite many clinical trials aimed at improving outcomes. Radiation therapy options for brain metastases include whole brain radiotherapy (WBRT) and stereotactic radiosurgery (SRS). SRS avoids the potential toxicities of WBRT and is associated with excellent local control (LC) rates. However, distant intracranial failure following SRS remains a problem, suggesting that untreated intracranial micrometastatic disease is responsible for failure of treatment. The oral alkylating agent temozolomide (TMZ), which has demonstrated efficacy in primary malignant central nervous system tumors such as glioblastoma, has been used in early phase trials in the treatment of established brain metastases. Although results of these studies in established, macroscopic metastatic disease have been modest at best, there is clinical and preclinical data to suggest that TMZ is more efficacious at treating and controlling clinically undetectable intracranial micrometastatic disease. We review the available data for the primary management of brain metastases with SRS, as well as the use of TMZ in treating established brain metastases and undetectable micrometastatic disease, and suggest the role for a clinical trial with the aims of treating macroscopically visible brain metastases with SRS combined with TMZ to address microscopic, undetectable disease.